1998
DOI: 10.1094/mpmi.1998.11.8.836
|View full text |Cite
|
Sign up to set email alerts
|

Tartrate Utilization Genes Promote Growth ofAgrobacteriumspp. on Grapevine

Abstract: Crown gall on grapevine is mainly caused by Agrobacterium vitis, which metabolizes tartrate. Competition experiments between a tartrate-utilizing strain and its non-utilizing derivative showed that tartrate utilization confers a selective advantage on grapevine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…Furthermore, competition experiments done in planta with one such strain and its tartrate-minus derivative showed that the TAR region provides a selective advantage for grape colonization (82). The ends of the TAR regions show no evidence for insertion sequences so that the ttu genes do not seem to be part ?…”
Section: Tartrate Utilization Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, competition experiments done in planta with one such strain and its tartrate-minus derivative showed that the TAR region provides a selective advantage for grape colonization (82). The ends of the TAR regions show no evidence for insertion sequences so that the ttu genes do not seem to be part ?…”
Section: Tartrate Utilization Plasmidsmentioning
confidence: 99%
“…Structure and function of A. vitis tartrate utilization region, TAR-I(81,82). This region is highly similar to that of TAR-II and TAR-III.…”
mentioning
confidence: 93%
“…L-Tartrate utilization by R. vitis is thought to play a role in host specificity (Szegedi 1985). On the other hand, R. radiobacter (Ti) isolated from host plants other than grapevine do not utilize L-tartaric acid, but some strains of R. radiobacter (Ti) isolated from grapevine do (Burr and Katz 1983;Salomone et al 1996Salomone et al , 1998Sawada and Tsuchiya 2003). Ten tumorigenic isolates identified as R. radiobacter (Ti) also utilized L-tartaric acid ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…It would be interesting to know what other functions tartrate plasmids carry. on grapevine, a species with high tartrate levels (Kado, 1998;Salomone et al, 1998). Strain AB3 carries two related tartrate utilization (tar) regions include detection of the pathogen in soils, the use of pathogen-free propagation material, biological control, and traditional or molecular breeding for new resistant varieties.…”
Section: Sources Of Infection and Control Of Crown Gall Diseasementioning
confidence: 99%